2023
DOI: 10.20945/2359-3997000000616
|View full text |Cite
|
Sign up to set email alerts
|

Use of the activPAL® triaxial accelerometer to estimate total energy expenditure in low-income women: differences between body mass index classifications

Abstract: Objective: This study aimed to assess the agreement between the total energy expenditure (TEE) estimated by the activPAL ® triaxial accelerometers (ACC) and the TEE measured by the doubly labeled water method (DLW), as well as to assess if these values differ between the classifications of body mass index (BMI). Materials and methods: This is a cross-sectional study. Low-income adult women (19-45y) with BMI ≥ 18.5 kg/m 2 were included. Accelerometry data (activPAL ® ) were collected over 7 consecutive days, wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 34 publications
0
1
0
Order By: Relevance
“…These data disagree with previous studies that reported accurate TDEE estimates (mean bias of ≅−2%) using measured BMR to determine PAL but using the 2005 DRI equations in a sample of 38 Brazilian older adults (Batista et al, 2021) and in 20 Brazilian women before bariatric surgery using accelerometry to estimate PAL (mean bias of 5%; Ravelli et al, 2018). Macena et al (2023) also reported accurate DRI ER estimation (mean bias of ≅−1.5%) in a sample of 55 low‐income overweight Brazilian women (mean age = 31.0 ± 5.4 years), but PAL was determined by accelerometry and BMR was not measured. An important feature of the new DRI equations is that they were developed to correct the interindividual variability of TDEE but data from non‐high‐income countries were excluded in the DRI equation development because of the differences in health, behavior, and environment in these countries, factors that might influence the ER calculations (NASEM, 2023).…”
Section: Resultsmentioning
confidence: 87%
“…These data disagree with previous studies that reported accurate TDEE estimates (mean bias of ≅−2%) using measured BMR to determine PAL but using the 2005 DRI equations in a sample of 38 Brazilian older adults (Batista et al, 2021) and in 20 Brazilian women before bariatric surgery using accelerometry to estimate PAL (mean bias of 5%; Ravelli et al, 2018). Macena et al (2023) also reported accurate DRI ER estimation (mean bias of ≅−1.5%) in a sample of 55 low‐income overweight Brazilian women (mean age = 31.0 ± 5.4 years), but PAL was determined by accelerometry and BMR was not measured. An important feature of the new DRI equations is that they were developed to correct the interindividual variability of TDEE but data from non‐high‐income countries were excluded in the DRI equation development because of the differences in health, behavior, and environment in these countries, factors that might influence the ER calculations (NASEM, 2023).…”
Section: Resultsmentioning
confidence: 87%